Secretory Duct Structure and Phytochemistry Compounds of Yellow Latex in Mangosteen Fruit - DORLY DORLY; SOEKISMAN TJITROSEMITO; ROEDHY POERWANTO; JULIARNI JULIARNI (HAYATI Journal of Biosciences, 2008)
Yellow latex is the main problem in mangosteen agribusiness, because it is one factor lowering the fruit quality. The structure of yellow latex secretory ducts in the flower and fruit as well as in the root, stem and leaf of mangosteen (Garcinia mangostana L.) seedling and the qualitative phytochemistry of yellow latex were studied. The ducts were branched, canal-like type. They were found in the exocarp, mesocarp, endocarp, aril of the fruit, flower, stem, and leaf. In the fruit, the biggest diameter of the secretory ducts was found in the endocarp. There were continuous secretory ducts from fruit stalk to the fruit. Ultrastructural observation showed that the ducts surrounded by specific epithelial cells, which were living cells containing dense cytoplasm with plastid, mitochondria and golgi apparatus organelles. The qualitative test indicated that the yellow latex collected from stem bark, outer part of fruit, young fruit pericarp, mature aril and young aril contained terpenoid, flavonoid and tannin, but not alkaloid, saponin and steroid, except in the young aril containing the steroid. Key words: secretory ducts, yellow latex, endocarp, aril, epithelial cells